2015
DOI: 10.1002/sam.11299
|View full text |Cite
|
Sign up to set email alerts
|

The fragility of standard inferential approaches in principal stratification models relative to direct likelihood approaches

Abstract: Many empirical settings involve the specification of models leading to complicated likelihood functions, for example, finite mixture models that arise in causal inference when using Principal Stratification (PS). Traditional asymptotic results cannot be trusted for the associated likelihood functions, whose logarithms are not close to being quadratic and may be multimodal even with large sample sizes. We first investigate the shape of the likelihood function with models based on PS by providing diagnostic tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…Therefore, they have superior statistical properties compared with principal stratification analysis based on normal mixture models, which have unbounded likelihood and inaccurate asymptotic normal distribution approximations as pointed out by Frumento et al . (). Furthermore, in our simulation studies which are shown in the on‐line supplementary material, we compare our method with the method of Jo and Stuart () involving outcome modelling and find that our estimator is not only robust to misspecification of the outcome model but also has smaller standard error.…”
Section: Modelling the Outcome And Model‐assisted Estimatorsmentioning
confidence: 97%
See 3 more Smart Citations
“…Therefore, they have superior statistical properties compared with principal stratification analysis based on normal mixture models, which have unbounded likelihood and inaccurate asymptotic normal distribution approximations as pointed out by Frumento et al . (). Furthermore, in our simulation studies which are shown in the on‐line supplementary material, we compare our method with the method of Jo and Stuart () involving outcome modelling and find that our estimator is not only robust to misspecification of the outcome model but also has smaller standard error.…”
Section: Modelling the Outcome And Model‐assisted Estimatorsmentioning
confidence: 97%
“…The tremendous variability of the estimator is due to the unstable numerical issue and unreliable large sample normal distribution approximation, as investigated by Frumento et al . ().…”
Section: Applicationsmentioning
confidence: 97%
See 2 more Smart Citations
“…Incorporating this structure is immediate with a Bayesian approach but can prove quite complex in a likelihood setting. In addition, accounting for uncertainty in the parameter estimates is natural with a Bayesian approach but can be more involved with a direct likelihood approach (see, for example, Frumento et al, 2016). While we use a Bayesian estimation approach, we would expect quite similar results using either method.…”
Section: Estimationmentioning
confidence: 97%